J. Baird Callicott, Science, and the Unstable Foundation of Environmental Ethics - Jean-Daniel Collomb (Angles)
This article analyzes the ideas of American philosopher J. Baird Callicott to shed light on ecological thinking and its inherent commitment to change and the adaptation of US environmental ethics. Callicott is one of the most prominent and longest-serving practitioners of environmental ethics; he is especially known for his support of land ethic, as defined by Aldo Leopold, and ecocentrism, an ethic predicated on the perception of ecosystems as communities. Callicott draws on the works of David Hume, Adam Smith and Charles Darwin to justify a Leopoldian ecocentrism. Extending Hume’s and Smith’s theory of moral sentiments to non-human life and ecosystems, Callicott claims to have continued Darwin’s ethical reflections in The Descent of Man (1871), also taken up by Aldo Leopold after his conversion to the ecological worldview. Callicott argues that the meaning of community can and must be protean, in order to ensure that environmental destruction will not continue unimpeded. Callicott thus calls for a major paradigm shift away from modernity, as defined by the scientific revolution of the 17th century, to a reconstructive postmodernity informed by Darwinism, ecology and the “new” physics spawned by quantum theory. According to Callicott, the only effective way to transcend Cartesian dualism is to bring about a major change in people’s worldview. Short of such a shift in paradigms, the dualities at the root of the environmental crisis will persist. Ironically, one of the main challenges to Callicott’s defense of the land ethic came from within ecology, from what Donald Worster calls the ecology of chaos. If Callicott rescues Leopold’s land ethic from ecological insignificance, this is because of the advent of disturbance ecology in the 1970s and 1980s along with the gradual replacement of the balance-of-nature paradigm by the nature-in-flux paradigm. How can ecosystems be considered communities if they are subject to stochastic and catastrophic change? Distinguishing the scale of non-human change and anthropogenic change, Callicott salvages an ethic whose ecological foundations are precarious and unstable. In doing so, he demonstrates that just as adaptation is part of a natural evolution, it is also the key to intellectual and philosophical evolution. Callicott’s response to disturbance ecology nevertheless highlights the precarious position of environmental philosophers who predicate their moral prescriptions on scientific knowledge, given that the science of ecology is always evolving.